Learning and collaboration technologies. novel learning ecosystems : 4th International Conference, LCT 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings /: novel learning ecosystems : 4th International Conference, LCT 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available